2011
DOI: 10.1161/strokeaha.110.599662
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Tirofiban in Acute Ischemic Stroke

Abstract: Background and Purpose— Tirofiban is a highly selective, fast-acting nonpeptide glycoprotein IIb/IIIa platelet receptor antagonist with a short half-life time. Glycoprotein IIb/IIIa antagonists are effective for the treatment of acute coronary syndromes proven in large clinical trials. Safety and efficacy in patients with ischemic stroke are uncertain. This was addressed in the Safety of Tirofiban in acute Ischemic Stroke (SaTIS) trial. Methods— Two hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 27 publications
3
96
2
3
Order By: Relevance
“…A SaTIS study comparing tirofiban with placebo on patients with NIHSS score of 4-18 has reported the average time length between the onset of symptoms and progression as 9.25 hours, whereas in our study, the mentioned average time length was determined as 27.85 hours (10). In the SaTIS study , the reliability and efficacy of tirofiban compared to placebo were assessed, but the early and long-term efficacy of the drug according to stroke subgroups were not evaluated (10).…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…A SaTIS study comparing tirofiban with placebo on patients with NIHSS score of 4-18 has reported the average time length between the onset of symptoms and progression as 9.25 hours, whereas in our study, the mentioned average time length was determined as 27.85 hours (10). In the SaTIS study , the reliability and efficacy of tirofiban compared to placebo were assessed, but the early and long-term efficacy of the drug according to stroke subgroups were not evaluated (10).…”
Section: Discussioncontrasting
confidence: 73%
“…The SaTIS study reported symptomatic intracerebral hemorrhage in 1.6% of the cases. In our study, symptomatic intracerebral hemorrhage did not occur in any of our patients (10). The macroscopic hematuria seen in two patients in the first 24 hours of the therapy was associated with use of urinary catheter.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations